The Design and Development of DSP Based Ring Main Unit FTU (Feeder Automation Terminal Unit) in Intelligent Distribution - Hong Zhou; Xing Luo; Qijun Deng (2010 International Conference on Electrical and Control Engineering, 2010)
RMU (Ring Main Unit) is small footprint, easy to use, but difficult to measure multiple analog signals, in response to these characteristics, this paper proposes a design of intelligent distribution ring main unit FTU (Feeder Terminal Unit) based on DSP. The system uses slot-type structure to carry on modular design, using CPLD for signal dispatching, it can measure up to 120 analog signals, digital signals can also be matched together, and it integrates a LCD for scene debugging. The system also developed a host computer debugging software based on the PC, the FTU can communicate with the host computer well through the serial port or the network, it is easy to learn the line's running status and the historical data on the PC. The system is compact and powerful, the prototype can use normally after test, the performance meets the estimate requirements.